Arsenite oxidation and (thio)arsenates formation in arsenite- and sulfide-containing solution under air atmosphere. (July 2022) - Zhang, Peiwen; Wang, Shaofeng; Zhang, Danni; Wang, Yumeng; Song, Yu; Jia, Yongfeng
Abstract: Thioarsenic species are widely existed in transitional environments with varying redox potential such as hot springs and paddy fields, where arsenite, sulfide and thioarsenites may be exposed to ambient air. However, arsenic speciation, especially the kinetics of arsenic transformation in such scenarios are not well studied. Here we present results from both kinetic experiments and computational information on the formation mechanisms of thioarsenic species from the sulfide-driven oxidation of arsenite (13.3 μM) under air atmosphere at circumneutral pH (6.5–10.5, covering the usual groundwater pH range). Ion chromatography-hydride generation atomic fluorescence spectrometry (IC-HG-AFS) was used for the determination of non-thiolated arsenic and thioarsenate species as well as indirect identification of thioarsenites at environmentally relevant As concentration. Results showed that the ambient air facilitated the thiolation and oxidation of arsenite, during which thioarsenites were served as intermediates. It was supported by our ab initio DFT calculation showing that the activity towards oxidation was in the order of: monothioarsenite > dithioarsenite > trithioarsenite > arsenite. The thiolation of arsenite was decreased with pH with a rate constant of 0.2–1.7 h −1 ; while the oxidation of thioarsenites by air was increased with pH with a rate constant of 0.1–0.45 h −1 . The results of this study shall improve our mechanistic understanding on the formation of thioarsenic, and shed light on the potential intermediate roles played by thioarsenites in environments with varying redox potential or intermittent anoxia, such as paddy fields, peatlands, hot springs etc. Graphical abstract: Image 1 Highlights: The concentration of thioarsenite species is indirectly estimated. Kinetic constants of arsenite thiolation and thioarsenites oxidation are determined. The reaction activity between (thio)arsenites and O2 is modeled by ab initio DFT. Intermediate role of thioarsenites in S(–II)-driven As(III) oxidation is revealed.